Prognostic factors for survival among gastric cancer patients receiving neoadjuvant chemotherapy: A cross sectional study from Turkey - Uzun, Orhan; Gülmez, Selçuk; Senger, Aziz Serkan; Öz, Ayhan; Özduman, Ömer; Ofluoğlu, Cem Batuhan; Polat, Erdal; Duman, Mustafa (Journal of Surgery and Medicine, 2020)
Aim: Gastric cancer is usually diagnosed once it has reached the advanced stage and is one of the leading causes of cancer-related deaths. We investigated the prognostic factors for survival among gastric cancer patients undergoing neoadjuvant chemotherapy to prolong overall survival. Methods: A retrospective review was made of patients who underwent surgery for gastric cancer between November 2006 and September 2019. Clinicopathological characteristics were assessed in 46 patients receiving neoadjuvant chemotherapy and 194 patients not receiving neoadjuvant therapy. A Cox regression analysis was used to assess the prognostic factors for survival among the patients receiving neoadjuvant chemotherapy. Results: The patients receiving neoadjuvant chemotherapy accounted for 19.2% of the total. The tumors in these patients were located primarily in the upper and middle portions (73.9%), to a statistically significant degree (P=0.001). There was no statistical difference in survival between the two groups, although a high number of positive lymph nodes was identified among the patients receiving neoadjuvant chemotherapy as the most significant prognostic factor for survival (P<0.01). Conclusion: After neoadjuvant chemotherapy, multiple positive lymph nodes are the most important prognostic factor for survival; postoperative chemotherapy protocol can be changed or other methods can be applied together with chemotherapy.